2018
DOI: 10.1159/000487489
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography-Driven Treat-and-Extend and Pro Re Nata Regimen in Patients with Macular Oedema due to Retinal Vein Occlusion: 24-Month Evaluation and Outcome Predictors

Abstract: Purpose: To analyse the efficacy and outcome predictors of ranibizumab using a spectral-domain optical coherence tomography (SD-OCT)-driven treat-and-extend regimen (TER) versus SD-OCT-driven pro re nata regimen (PRN) in patients with cystoid macular oedema (CME) due to branch or central retinal vein occlusion (BRVO, CRVO). Methods: Retrospective, consecutive case series. Evaluation included best corrected visual acuity (BCVA), morphological parameters on SD-OCT, and treatment frequency. Results: From baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…This could include instituting maximum treatment intervals greater than 12 weeks or prolonging treatment with a 12-week interval for a longer period, as done for the TAE regimen used in patients with age-related macular degeneration [ 16 ]. A previous study demonstrated the mean number of injections within 12, 18, and 24 months was significantly higher in the TAE regimen than in the PRN regimen in the treatments for retinal vein occlusion patients [ 17 ]. In fact, the mean number of injections within 12 months (6.6 ± 1.7, median: 7 [IQR, 5–7]) in our TAE regimen was higher than the mean number of injections within 12 months (4.0 ± 1.8) reported in the previous study with the PRN regimen [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could include instituting maximum treatment intervals greater than 12 weeks or prolonging treatment with a 12-week interval for a longer period, as done for the TAE regimen used in patients with age-related macular degeneration [ 16 ]. A previous study demonstrated the mean number of injections within 12, 18, and 24 months was significantly higher in the TAE regimen than in the PRN regimen in the treatments for retinal vein occlusion patients [ 17 ]. In fact, the mean number of injections within 12 months (6.6 ± 1.7, median: 7 [IQR, 5–7]) in our TAE regimen was higher than the mean number of injections within 12 months (4.0 ± 1.8) reported in the previous study with the PRN regimen [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of clinic visits was similar to that in the TAE regimen [ 18 , 19 ]. Many previous studies investigated PRN and TAE regimens for BRVO [ 7 , 8 , 10 , 11 , 18 , 19 , 22 ], but this mTAE regimen is the first to combine the best features of PRN and TAE regimens.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, the TAE and as-needed approaches have been compared in eyes with all types of RVO, with no significant differences in VA found at 12 months. 29…”
Section: Discussionmentioning
confidence: 99%
“…Guichard et al 29 compared the TAE and as-needed approaches, each initiated after 1 ranibizumab injection at baseline, in eyes with macular edema associated with any type of RVO and found that mean number of injections in the first 12 months was 9.6 ± 2.0 and 4.2 ± 1.8 for TAE and as-needed approaches, respectively. Other studies have found similar results, with 1-year injection counts of 8 to 10 for the TAE approach of CRVO.…”
Section: Discussionmentioning
confidence: 99%